1998
DOI: 10.1021/ja981805y
|View full text |Cite
|
Sign up to set email alerts
|

New Catalytic Properties of Iron Porphyrins: Model Systems for Cytochrome P450-Catalyzed Dehydration of Aldoximes

Abstract: Various iron porphyrin systems were found to catalyze the dehydration of aldoximes, such as heptanaldoxime or phenylacetaldoxime, into the corresponding nitriles under mild conditions (t ) 20 °C, neutral or slightly acidic pH). In all these systems, the presence of both the iron porphyrin catalyst and a reducing agent is required, indicating that the active species is the iron(II) porphyrin. The most efficient systems used either an organosoluble iron porphyrin, such as Fe(OEP), in the presence of a carboxylic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…The possible mechanism shown in Fig. 5 is largely in accordance with the results of studies on various iron porphyrin systems by Mansuy and coworkers (48,49), suggesting that the ferryl state is formed in the aldoxime dehydration cycle.…”
supporting
confidence: 87%
“…The possible mechanism shown in Fig. 5 is largely in accordance with the results of studies on various iron porphyrin systems by Mansuy and coworkers (48,49), suggesting that the ferryl state is formed in the aldoxime dehydration cycle.…”
supporting
confidence: 87%
“…140,141 The consensus rebound mechanism, 148 suggested by Groves et al,151,152,160 corresponds to reactions from species 2 to 4. This involves initial hydrogen abstraction from the alkane (R-H) by the active ferryloxene species (2, Por + Fe IV -O, Por = porphyrin), known also as Compound I, 148,[161][162][163][164][165][166] followed by radical rebound on the ferryl-hydroxo intermediate, 3, to generate the ferric-alcohol complex 4. While the intermediacy of the precursor hydroperoxy complex 1 has recently been ascertained by electron nuclear double resonance (ENDOR) spectroscopy under turnover conditions, 150 compound I (2) remains elusive and the mechanism of hydroxylation is still controversial.…”
Section: Hydroxylation Reaction Catalyzed By Cytochrome P450mentioning
confidence: 99%
“…However, from results obtained with various iron porphyrin systems and rat liver microsomal cytochromes P450, respectively (31,60), it is suggested that the first step of aldoxime dehydration comprises binding of the aldoxime nitrogen atom to the heme iron, the following step (the ratedetermining step) comprises abstraction of the OH group of aldoxime, which is due to protonation of the OH group by an acidic amino acid residue, and the final step comprises elimination of a hydrogen atom on the carbon neighboring the nitrogen atom of aldoxime.…”
Section: Hismentioning
confidence: 99%